COMPARISON OF THE VALUE PERCEIVED BY CUSTOMERS AND MANAGERS ABOUT THE SERVICES PROVIDED BY FITNESS CENTERS - Vinicius Almeida Calesco; Jorge Both; Jeane Barcelos Soriano (Universidade Estadual do Oeste do Paraná, 2013)
The objective was to compare the value perceived of the importance and performance of fitness centers by the view of administrators and customers. The sample was integrated with 123 individuals, 108 customers and 15 managers of 10 gyms of Londrina / Paran. For the date collecting was applied a questionnaire that was constructed for this investigation. For the statistical analysis was applied the Kolmogorov-Smirnov test to verify the normal distribution of the data, which was not identified. Thus, was applied the test U of Mann-Whitney, considering a confidence level of 95% (p 0,05). The results showed that customers have lower rates of importance in issues as the communication between professionals from gym and customers (p = 0.02), the teamwork of professionals from gym (p = 0.03) and the enhancement of older customers (p = 0.03). Finally, it is concluded that fitness centers administrators overestimate the importance of the services provided by the gym.